Initial Boundary Value Problem for Generalized 2D Complex Ginzburg-Landau Equation (Journal of Partial Differential Equations, 2007)
In this paper we study an initial boundary value problem for a generalized complex Ginzburg-Landau equation with two spatial variables (2D). Applying the notion of the ε-regular map we show the unique existence of global solutions for initial data with low regularity and the existence of the global attractor.
Keywords: Generalized 2D Ginzburg-Landau equation; initial boundary value problem; ε-regular map; global solution; global attractor